Laboratory Biomarkers in the Management of Patients With COVID-19. Issue 3 (27th October 2020) - Weidmann, Maxwell D; Ofori, Kenneth; Rai, Alex J
Abstract: Objectives: Laboratory testing and the measurement of appropriate biomarkers play a critical role in managing patients with coronavirus disease 2019 (COVID-19), allowing for disease diagnosis, monitoring progression, prognostication, prediction of treatment response, and risk stratification. We sought to characterize these effects on a more detailed, mechanistic level. Methods: We reviewed the literature and identified a multitude of reports that describe the unique effects of this virus and its devastating consequences to multiple organ systems in COVID-19 patients. Results: There are specific alterations in biomarkers related to coagulation, depopulation of T-cell subtypes, the cytokine storm and inflammation, and kidney and cardiac dysfunction. Conclusions: Laboratory measurement of specific parameters and the use of appropriate prognostic, predictive, and monitoring biomarkers afford clinicians the ability to make informed medical decisions and guide therapy for patients afflicted with this dreaded disease.